Effects of postural threat on the scaling of anticipatory postural adjustments in young and older adults - Phanthanourak, Angel L.; Adkin, Allan L.; Carpenter, Mark G.; Tokuno, Craig D. (Frontiers in Human Neuroscience, 2023)
Introduction: The ability to scale anticipatory postural adjustments (APAs) according to the predicted size of the upcoming movement is reduced with aging. While age-related changes in central set may be one reason for this effect, an individual's emotional state might also contribute to changes in anticipatory postural control. Therefore, the purpose of this study was to determine whether an altered emotional state, as elicited through postural threat, alters the scaling of APAs during a handle pull movement in young and older adults. It was hypothesized that the presence of postural threat would lead to more homogenous APAs (i.e., less scaling of APAs) across a range of pulling forces.Methods: Young (n=23) and older adults (n=16) stood on top of a force plate that was mounted to a motorized platform. From this position, participants performed a series of handle pull trials without (no threat) or with (threat) the possibility of receiving a postural perturbation in the form of an unpredictable surface translation. Handle pulls were performed at force levels between 50% and 90% of maximum force. For each trial, the magnitude and timing of the APA were quantified from center of pressure (COP) recordings as well as electromyographic (EMG) activity of the soleus and medial gastrocnemius. The scaling of APAs with respect to force exertion was then determined through regression analyses and by comparing APAs during pulls of lower versus higher force.Results and Discussion: As evidenced by their smaller slope of the regression line between various dependent measures (i.e., COP velocity, soleus EMG onset latency, and soleus EMG amplitude) and the pulled forces, older adults demonstrated less scaling of APAs than the young. However, increases in arousal, anxiety and fear of falling due to postural threat, only minimally altered the scaling of APAs. Regardless of age, the slope of the regressions for none of the measures were affected by threat while only the soleus and medial gastrocnemius EMG onsets demonstrated significant force x threat interaction effects. These results suggest that the decreased ability to scale APAs with aging is unlikely to be due to changes in emotional state.